Helicobacter pylori: Basic Mechanisms to Clinical Cure - ABR Thomson; CN Williams (Canadian Journal of Gastroenterology)
Since its rediscovery 10 years ago, Helicobacter pylori has reshaped our thinking about the course of peptic ulcer disease. Our approach to the patient with a duodenal ulcer has become one of attempting eradication therapy at the time of first diagnosis, in the hope of curing the ulcer disease. Gastric and duodenal ulceration are only two of the manifestations of this chronic antral infection; other complications of H pylori include gastritis, gastric cancer and possible maltomas. Therapy of H pylori infection is complicated and involves dual therapy with an antibiotic plus a protein pump inhibitor, such as omeprazole 20 mg bid plus amoxicillin 1 g bid for two weeks, triple or quadruple therapy with bismuth, two antibiotics and an H2-receptor antagonist. Vaccination against H pylori is on the far horizon.